The imbalance between Type 17 T-cells and regulatory immune cell subsets in psoriasis vulgaris - Kim, Jaehwan; Moreno, Ariana; Krueger, James G. (Frontiers in Immunology, 2022)
Psoriasis vulgaris is a common inflammatory disease affecting 7.5 million adults just in the US. Previously, psoriasis immunopathogenesis has been viewed as the imbalance between CD4+ T-helper 17 (Th17) cells and CD4+ CD25+ FOXP3+ regulatory T-cells (Tregs), where Tregs have been considered the primary regulatory cells maintaining immune tolerance in the skin. However, current paradigms are rapidly evolving as new technologies to study immune cell subsets in the skin have been advanced. For example, recently minted single-cell RNA sequencing technology has provided the opportunity to compare the transcriptomes of T cell subsets that commonly produce IL-17 isoforms (T17 cells) or CD25+ FoxP3 (Tregs). Subsequently, it is now recognized that cutaneous T17 cell subsets exist within CD4+, CD8+, and CD161+ subpopulations with highly differing transcriptomes depending on IL-17A vs. IL-17F expression. A comparison of the single-cell transcriptomes of T17 cell subsets identified that the psoriasis IL-17F+ T17 cell subset transcriptome includes expression of FoxP3 and other regulatory cytokines, providing evidence of T-cell plasticity between T17 cells and regulatory T cells in humans. In addition to Tregs, other types of regulatory cells in the skin have been elucidated, including type 1 regulatory T-cells (Tr1 cells) and regulatory semimature/BDCA-3+ dendritic cells. More recently, investigators are attempting to apply single-cell technologies to clinical trials of biologics to test if monoclonal blockade of pathogenic T-cells will induce expansion of regulatory T-cells or regulatory dendritic cells or expression of cytokines involved in skin homeostasis.